Kualitas Fisik Tanah pada Berbagai Tipe Penggunaan Lahan di Desa Mayangan Kecamatan Gumukmas - (:unkn) unknown (Fakultas Pertanian, 2025)
Soil quality is the ability of soil to perform its functions, and it can be assessed through various aspects, including its physical quality. Physical soil quality plays an important role in supporting the availability of nutrients and the soil's capacity to store water for living organisms. Mayangan Village, located in Gumukmas Subdistrict, is a coastal area with soils dominated by sand fractions, making the aspect of physical soil quality a primary concern in this region. The research problem in this study is to determine the physical soil quality across various land use types in Mayangan Village, Gumukmas Sub-district. This study aims to assess the physical soil quality index under different land use types in Mayangan Village. The method used in this research was Principal Component Analysis (PCA) to process the physical soil quality variables in each land use type, including yard, dry field, tidal swamp, lowland swamp, irrigated rice field, shrub, fishpond, and forest. The results showed that the physical soil quality in Mayangan Village varies across different land use types. Yard areas have low to moderate physical soil quality, while lowland swamps, tidal swamps, irrigated rice fields, and fishponds are categorized as low. Shrub areas are categorized as moderate, while dry fields fall under the very low to low category. This study concludes that the physical soil quality in Mayangan Village is predominantly categorized as low. Therefore, efforts to improve soil quality through the application of biochar and soil amendments are necessary to support the sustainability of soil productivity in Mayangan Village.
Entry oleh Arif 2026 Januari 28
Keywords: Land use types; Mayangan Village; physical soil quality